Pengaruh Kondisi Sosial Ekonomi terhadap Pemenuhan Kebutuhan Pendidikan Siswa SMK Negeri 2 Kasongan Kabupaten Katingan: Peran Mediasi Dukungan Orang Tua - Sri Wahyuni; Yossita Wisman; Ujen Zenal Mikdar (Jurnal Ilmiah Kanderang Tingang, 2026)
This study examines the socio-economic conditions of students’ parents and their implications for fulfilling educational needs in a vocational school context. The research was conducted at SMKN 2 Kasongan, Katingan Regency, Indonesia, where students come from diverse socio-economic backgrounds. A qualitative descriptive approach was employed, involving purposively selected informants, including parents, students, teachers, and school administrators. Data were collected through in-depth interviews, observations, and document analysis, and analyzed using an interactive model of data reduction, data display, and conclusion drawing. The findings reveal that most parents belong to lower-middle socio-economic groups, characterized by low educational attainment, informal employment, and unstable income. These conditions limit students’ ability to access learning resources and meet practical training requirements, which are essential in vocational education. However, the study also finds that parental support—particularly in the form of motivation and educational commitment—plays a significant mediating role in mitigating the negative effects of economic constraints. Furthermore, the vocational education context intensifies the impact of socio-economic disparities due to its resource-intensive learning demands. This study contributes to the literature by highlighting that socio-economic status does not operate deterministically; instead, it interacts with parental involvement and institutional support in shaping students’ educational experiences. The findings suggest that schools should strengthen inclusive support systems and targeted assistance programs to reduce educational inequality, particularly in vocational settings in rural or underdeveloped areas.